FILSAFAT ANALITIKA BAHASA: Urgensi Filsafat Bahasa Dalam Landasan Filosofis Pembelajaran Bahasa Arab - Dinata, Rahmat Satria; Budiarti, Meliza; Musalwa, Musalwa (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The emergence of the analytic philosophy of language that developed by Ludwig Wittgenstein focused that the problem of philosophy is a problem of language. Philosophy of language as a linguistic discipline has a strategic position related to the development of language learning, including Arabic. By using library research methods, this study aims to describe the urgency of the philosophy of language and Arabic learning which resulted in several conclusions. First, in essence, language is a symbol system that is not only a sequence of empirical sounds but has a non-empirical meaning. Second, the relationship between philosophy and language occurs when philosophers most often use language analysis to solve philosophical problems. Third, the position of philosophy as the basis for analyzing language concepts and considering the central role of language in verbally expressing philosophical thoughts. Fourth, Arabic learning is in dire need of a philosophical foundation